Synthesis and Spectral Studies of Thorium(IV) and Dioxouranium(VI) Complexes of Schiff Base Derived from Benzocain and p-Dimethyl Amino Benzaldehyde - Arora, Kishor (Asian Journal of Chemistry, 2012)
A new series of complexes of Th(IV) and UO2(VI) with a Schiff base derived from condensation of benzocain and p-dimethylamino benzaldehyde having general composition ThX4.nL (X = Cl–, Br–, NCS– or I–, n = 4; X – ClO4–, n = 6; X = NO3–, n = 2) and UO2X2.2L (X = NO3–, Br–, I–, NCS– and CH3COO–) or UO2X2.4L (X = ClO4–, where L is Schiff base. The complexes were characterized on the basis of elemental analysis, molecular weight determination, magnetic moment, infrared and electronic spectral studies and conductivity measurements. In all the complexes, ligand behaves as monodentate neutral ligand which coordinate to metal by azomethine nitrogen.